Nutritional Merits of a Ginger-Spiced Cheese Fed to Male Wistar Rats - Mendi, S.D.; Nain, C.W.; Mfopit, M.Y.; Tanya, A.; Carl, M.F. (Pakistan Journal of Nutrition, 2009)
The aim of this study was to evaluate the nutritional merits of ginger-spiced cheese in terms of body weight gain and feed utilization, blood lipid profile and implantation of micro-organisms in the gastrointestinal tract of consumers. Four groups of male Wistar rats of 9 per group housed 3 per cage were fed for four weeks. Three of the groups were supplemented with ginger-spiced cheese of 0, 1.0 and 1.5 g ginger powder/100 g of milled curd while the control group did not receive any cheese supplement. The rats were weighed before the start of cheese supplementation and thereafter, every week. The rats were sacrificed and blood was collected and triglycerides, total cholesterol, HDL and LDL cholesterol were determined. There was the enumeration of total bacterial colonies, yeasts and moulds and Lactobacilli colonies from the intestinal contents of the rats. Results showed that body weight gain and feed efficiency ratio were significantly (p